Standardization of choroidal thickness measurements using enhanced depth imaging optical coherence tomography - Boonarpha, N; Zheng, Y; Stangos, AN; Lu, H; Raj, A; Czanner, G; Harding, SP; Nair-Sahni, J (IJO Press, 2015)
AIM: To describe and evaluate a standardized protocol for measuring the choroidal thickness (ChT) using enhanced depth imaging optical coherence tomography (EDI OCT). METHODS: Single 9 mm EDI OCT line scans across the fovea were used for this study. The protocol used in this study classified the EDI OCT images into four groups based on the appearance of the choroidal-scleral interface and suprachoroidal space. Two evaluation iterations of experiments were performed:first, the protocol was validated in a pilot study of 12 healthy eyes. Afterwards, the applicability of the protocol was tested in 82 eyes of patients with diabetes. Inter-observer and intra-observer agreements on image classifications were performed using Cohen’s kappa coefficient (k). Intraclass correlation coefficient (ICC) and Bland-Altman’s methodology were used for the measurement of the ChT. RESULTS: There was a moderate (k=0.42) and perfect (k=1) inter- and intra-observer agreements on image classifications from healthy eyes images and substantial (k=0.66) and almost perfect (k=0.86) agreements from diabetic eyes images. The proposed protocol showed excellent inter- and intra-observer agreements for the ChT measurements on both, healthy eyes and diabetic eyes (ICC>0.90 in all image categories). The Bland-Altman plot showed a relatively large ChT measurement agreement in the scans that contained less visible choroidal outer boundary. CONCLUSIONS: A protocol to standardize ChT measurements in EDI OCT images has been developed; the results obtained using this protocol show that the technique is accurate and reliable for routine clinical practice and research.